Utilization of Immersive Virtual Reality in Cognitive Stimulation Therapy (IVR-CST) for elderly with mild cognitive impairment: A randomized controlled pilot study protocol - Winsy Wing Sze Wong; Gloria Hoi Yan Wong; Jacky Chak Pui Choy; Donald Shi Pui Li; Yee Lam Lo (PLoS ONE, 2025)
Objectives Mild cognitive impairment (MCI) affects about 11.4% of the elderly population in Hong Kong. This study mainly investigates the feasibility and efficacy of immersive virtual reality-based cognitive stimulation therapy (IVR-CST) on MCI, and the use of eye-tracking technology in studying treatment outcome. Hypothesis to be tested 1) Whether IVR-CST is a feasible intervention for the elderly with MCI. 2) Whether IVR-CST is efficacious (and more efficacious than conventional CST) in improving cognition. 3) Whether changes in eye movements across therapy and treatment outcome are associated. Design and subjects An open-label, two-armed, assessor-blinded, randomized controlled trial will be conducted. Sixty-six elderly individuals with MCI will be recruited and randomly allocated to either the IVR-CST or the conventional CST group. Their cognition will be measured before and immediately after therapy and 4 weeks post-therapy. Interventions A 14-session IVR-CST or conventional CST, with content adapted from the Chinese-translated manual of CST, will be carried out twice per week in groups of three to four individuals. Outcome measures and data analysis The Hong Kong Montreal Cognitive Assessment and measures on executive functions/working memory will serve as primary outcomes. The within-subject (before and after therapy) and between-subject (IVR-CST vs. conventional CST) differences will be examined. Besides, eye movements during therapy in the IVR-CST group will be collected and its correlation with primary outcomes will be studied. Expected results Positive changes in cognition are expected after therapy in both treatment groups, which may be maintained four weeks post-therapy. Trial registration ClinicalTrials.gov ID: NCT06838494